Hábitos alimentarios y actividad física de los estudiantes de la Universidad Iberoamericana del Ecuador (UNIB.E) - Ordoñez-Araque, Roberto; CAICEDO JARAMILLO, Carla; GESSA GÁLVEZ, Meybol (Nutrición Clínica y Dietética Hospitalaria, 2021)
Eating habits and physical activity are fundamental factors that influence society’s health, today all over the world there are obesity and overweight problems, precisely due to the lack of physical exercise and poor dietary regime of people. Due to this reason, it is essential to carry out studies to identify these types of problems and carry out health prevention programs. Objective: The objective of this research was to evaluate the eating habits (EH) and physical activity (PA) of the students of the Universidad Iberoamericana del Ecuador. Methods: This study was carried out with 50% of university students; they were divided into two groups (G1-G2) according to the number of students enrolled for each degree. A validated questionnaire (consisting of 3 sections for EH and 1 section for PA) was used. The results were evaluated with descriptive statistics for the interpretation of the questionnaire. To analyze whether there was a significant difference between G1 and G2 results, the Student’s t-test was performed with a level of statistical significance of p < 0.05. Results: According to the instrument used, 72.6% of low consumption of adequate foods (fruits, vegetables, white yogurt, etc.), 54.3% of high consumption of inappropriate foods (sausages, snacks, sugary drinks, etc.), and 76.4% of adequate eating behavior (company, place and time of consumption) were obtained. In general, the students’ EH is partially inadequate (70.2%) and predominates the inadequate PA (60.6%). There were no significant differences between G1 and G2, except for eating behavior, with a higher average for G2 than G1. Conclusions: There is a problem with eating habits and physical activity in UNIB.E students; the results obtained can be assumed for other higher education institutions in Ecuador. It is vitally important that public and private authorities generate prevention awareness campaigns for proper nutrition and health to avoid future diseases.